In Vivo Genotoxicity Assessment of Gold Nanoparticles of Different Doses by Comet Assays - Zainab Ahmad Hassan1 , Hind Hussein Obaid2 , Mustafa Nuhad al-Darraji3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gold nanoparticles were synthesis by green method using the soaked orange peels (citrus Sinensis) as reducing and stabilizing agent. The gold nanoparticles were diagnosed using the approved method, including the transmission electron microscope and the visible UV spectroscopy. Thus, the results of the diagnosis showed the formation of spherical particles with a size of 36 nanometers. Their biological effects on the bone marrow cells of albino mice were studied. Male albino mice were used in this study and randomly divided into seven groups. The first group was the control group injected with the physiological solution (Normal Saline) and the other six groups were injected with different doses of the solution of the gold nanoparticles (1, 2, 4, 6, 8 and 10) Mg/kg. The effect of gold nanoparticles on the DNA damage by bone marrow cells was studied using comet assay according to the following criteria: (DNA in Head%, Comet Length, Tail Length, DNA in Tail%, Olive Moment), the results showed a significant decrease (P?0.01) in the rate of DNA in Head%, while it showed a significant increase in Comet Length, Tail Length, DNA in Tail%, Olive Moment compared to the control group and all Doses studied. The effect of gold nanoparticles was directly proportional to the increase in the studied doses. The dose was 10 mg/kg, which was the highest toxicity, followed by the dose of 8 mg/kg, then the rest of the doses was descending.